Study on the Factors to Improve Productivity and Efficiency of Construction Workers in Klang Valley - Hoo, Boon Xyan; Khalid, Zailawati; Saarani, Puteri Sidrotul Nabihah; Sarpin, Norliana; Omar, Roshartini (Research in Management of Technology and Business, 2024)
The construction industry is one of the fastest growing industries, with a labor shortage and low productivity and efficiency among construction workers. To discover the elements impacting labor productivity on the progress of construction work, this research has been conducted in order to give approach and exposure to the construction industry. However, worker productivity has a disadvantage in terms of improving building progress. A specific issue is the lack of skilled workers, lack of building experts and lack of communication in the construction industry. Consequently, there are three objectives of the study carried out in this research which is to determine the important element for improvement of productivity and efficiency, to investigate the factors that decrease productivity and efficiency and to suggest the methods to improve construction workers productivity and efficiency in construction industry. This research focused on the construction workers in the Klang Valley’s area. Total construction workers in the Klang Valley are 3424 workers, so the sample size is 346. The respondents were given a questionnaire by a link of google form through WhatsApp, Instagram and Email. A total of 184 respondents (53.18%) had given feedback in the questionnaire. Frequency analysis was used to analyses the demographic of respondents while Cronbach alpha, mean and frequency was used to analyses the data for all objectives. This research found that the important element for improvement the productivity and efficiency of construction workers are rewards while the factors that decrease productivity and efficiency of construction workers are low wages. Lastly is the method to improve construction workers productivity and efficiency in construction industry is send to construction training centre that provided by CIDB. In addition, this study has significant to improve the productivity and efficiency of construction workers in construction industry.